EVALUATION OF NON-POINT SOURCE HEAVY METAL POLLUTION ON A DRAINAGE NETWORK OUTLET - Erewari Ukoha-Onuoha; Charity Chisa Dike (Journal CleanWAS)
This study assessed the impact of road runoff on the ecological risk of heavy metals in the Eagle Island River. Runoff samples were collected from a drainage network of secondary and primary drains and an outlet. The drains were situated in the Rivers State University, Port Harcourt campus while the outlet is the Eagle Island River. Samples from the secondary drain, primary drain, upstream and downstream of outlet were labelled as SD, PD, US, and DS respectively. Samples were collected and analyzed using standard methods between the months of August and October, 2023. Heavy metals including Cd, Cr, Cu, Pb, and Zn were analyzed using Atomic Absorption Spectrophotometer Instrument (GBC XplorAA, Australia). Total pollution of heavy metals was determined using the degree of contamination (Cd) and the modified degree of contamination (mCd) while the potential ecological risk was assessed by the Risk Index (RI). Results showed spatial variation of heavy metal concentration along the drainage network and Cd and Pb concentrations in all samples exceeded the WHO guideline. Cd and mCd values ranged between 22.20 – 88.70 and 4.44 – 17.74 respectively while the RI values ranged between 217.72 – 609.53. This implies that the entire drainage network was polluted by heavy metals and Cd and Pb were largely responsible for the pollution load with Cd contributing a range of 7.75% – 26.46% while Pb contributed 66.88% – 90.14%. Cd and Pb are carcinogenic, therefore storm runoff treatment is recommended for environmental sustainability.